Groundwater quality assessment for drinking and clean water in Bagelen and its surrounding area - T. Listyani R.A.; Thomas Triadi Putranto (Sustinere: Journal of Environment and Sustainability, 2022)
Bagelen and its surrounding area are parts of the Kulon Progo Hills which have less water potential. However, groundwater can still be obtained from dug wells or several springs in the hills. This study aims to determine the quality of groundwater in the study area as clean water and drinking water. Hydrogeological surveys have been conducted to see the quality of this groundwater. Groundwater samples were taken from six dug wells and two springs. Groundwater can be found in sandstone, limestone and andesite breccias aquifers, through intergrains and cracks porosities. Groundwater usually has Ca-bicarbonate facies. The need for good quality groundwater for drinking and clean water has been investigated based on the WQI value. The WQI value is determined based on several physical parameters, including turbidity and TDS and chemical parameters such as pH, Fe, hardness, Mn, nitrate, Zn, sulfate, chloride and sodium. Based on the Minister of Health Regulation standard No. 492/2010 for drinking water and No.Â  32/2017 for clean water, the groundwater showed good - excellent value for drinking water and excellent value for clean water.